Simple Removal of Ventriculoatrial Shunt and Simultaneous Ventriculoperitoneal Shunt Revision: Short Communication - Oike, Ryo; Inoue, Yasuaki; Matsuzawa, Kazuhito (Indian Journal of Neurosurgery, 2021)
Background  Ventriculoatrial shunt (VAS) is a common alternative treatment option for hydrocephalus in patients with ventriculoperitoneal shunt (VPS) failure. Most previous reports on VAS discuss the atrial-related complications and none focus on simple removal (i.e., without specialized equipment). We report a case of simple VAS removal and simultaneous VPS revision, with no obvious shunt-related cardiac complications.Case presentation  The patient was an 87-year-old female who had received a VAS for idiopathic normal pressure hydrocephalus 6 years prior. She developed a right thalamic hemorrhage with intraventricular hemorrhage and was admitted to our hospital. She had a recurrence of the hydrocephalus and was diagnosed with shunt malfunction, due to simple obstruction without obvious shunt-related cardiac complications. The VAS was simply and safely removed, and a VPS was simultaneously placed, as per the usual procedure in our institution. She remains well with no evidence of complications on postoperative day 10.Discussion  Since VAS is mostly used in pediatric cases that are difficult to treat with VPS, the duration of time elapsed allows VAS catheters to form strong adhesions with the surrounding cardiac tissue. Therefore, the simple removal of VAS is usually not straightforward.Conclusion  If the follow-up period is short and there are no specific cardiac complications at the time of replacement, VAS can be safely removed and VPS can be spontaneously placed, without any specialized surgical techniques or equipment.
Keywords: Ventriculoatrial shunt; ventriculoperitoneal shunt; hydrocephalus